2016
DOI: 10.1155/2016/4289736
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Pseudopapillary Tumor of the Pancreas: A Single Center Experience

Abstract: Aim of this study was to review the institutional experience of solid-pseudopapillary tumors of the pancreas with particular attention to the problems of preoperative diagnosis and treatment. From 1997 to 2013, SPT was diagnosed in 18 patients among 451 pancreatic cystic neoplasms (3.7%). All patients underwent preoperative abdominal ultrasound, computed assisted tomography, and tumor markers (CEA and CA 19-9) determinations. In some instances, magnetic resonance, positron emission tomography, and endoscopic u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…Needless to say, no IHC profile is pathognomonic for the diagnosis of SPN, and much overlap in expression exists among the aforementioned tumors. The associated prognosis and necessary treatment modalities vary widely for each neoplasm, and therefore a combination of morphologic and IHC findings is of paramount importance …”
Section: Discussionmentioning
confidence: 99%
“…Needless to say, no IHC profile is pathognomonic for the diagnosis of SPN, and much overlap in expression exists among the aforementioned tumors. The associated prognosis and necessary treatment modalities vary widely for each neoplasm, and therefore a combination of morphologic and IHC findings is of paramount importance …”
Section: Discussionmentioning
confidence: 99%
“…The detailed search strategy is depicted in Fig 1. A total of 98 studies were identi ed [4][5][6][7] . All studies were retrospective in nature.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of SPTM was reported in 22 articles [6,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Meta-analysis results suggested that the incidence of SPTM in solid pseudopapillary tumors of the pancreas was 22% [95%CI: 19-24%] (…”
Section: Incidence and Predictive Factors Of Sptmmentioning
confidence: 99%
See 1 more Smart Citation
“…CTNNB1 somatic mutation on exon 3 is the only known mutation in SPN to date. Like most tumours, when they are small, they are detected incidentally in imaging (USG, MRI, CT) [13][14][15][16][17][18]. Large tumours cause abdominal pain, abdominal discomfort, low-grade fever weight loss, and anaemia, and haemorrhage to the tumour may present a symptom of acute abdomen.…”
Section: Discussionmentioning
confidence: 99%